Pagan Rome was Rebuilt in a Play: Roggero Musmeci Ferrari Bravo and the Representation of Rumon - Giudice, Christian (Pomegranate, 2014)
Outside of its national boundaries, studies regarding twentieth-century Italian occultism have been sorely lacking. While the role of occultism and occultists in modern nations such as England, Germany, France and the United States, has been studied in detail, the events and main characters that influenced the esoteric circles in early twentieth-century Italy have been mostly neglected or relegated to very cursory enquiries. It is my intention, in this paper, to focus on the theme of a Pagan new beginning for the newly reunited Italy, first sketching a historical portrayal of the influence the idea of Ancient Rome had on both artists and occultists, then focusing, by utilising recently discovered archival material, on poet and playwright Roggero Musmeci Ferrari Bravo and his tragedy on the birth of Rome, Rumon Sacrae Romae Origines, viewing the play as an attempt to mass-initiate the auience to the alleged palingenetic virtues of Roman traditionalism, in view of a new Italian renaissance.